2010
DOI: 10.1097/ta.0b013e3181c4539f
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With a Sepsis Bundle and Its Effect on Intensive Care Unit Mortality in Surgical Septic Shock Patients

Abstract: In surgical septic shock patients, the outcome was significantly related to the number of fulfilled therapeutic guidelines included in a sepsis bundle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Our study confirms previous reports that the rate of bundle compliance is different between regions [4,17] and confirms the ability of sites in North America to perform the initial (3-h) resuscitation bundle elements better that other regions, but also suggests that Western Europe has higher compliance with the 6-h elements. In addition we have confirmed the reports that compliance with these tools improves outcome even when taking into account all presenting differences [4,17,23,25,27,28]. In conclusion we have observed in a large multinational observational study that compliance with evidencebased bundle metrics designed to improve outcomes from septic shock remains low, varies significantly between different geographical regions and when performed is associated with improvements in outcome.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our study confirms previous reports that the rate of bundle compliance is different between regions [4,17] and confirms the ability of sites in North America to perform the initial (3-h) resuscitation bundle elements better that other regions, but also suggests that Western Europe has higher compliance with the 6-h elements. In addition we have confirmed the reports that compliance with these tools improves outcome even when taking into account all presenting differences [4,17,23,25,27,28]. In conclusion we have observed in a large multinational observational study that compliance with evidencebased bundle metrics designed to improve outcomes from septic shock remains low, varies significantly between different geographical regions and when performed is associated with improvements in outcome.…”
Section: Discussionsupporting
confidence: 74%
“…This study is the first report of compliance with the 2012 SSC bundles [7] and as such adds to the literature supporting this methodology for quality improvement [4,17,[27][28][29]. Our study confirms previous reports that the rate of bundle compliance is different between regions [4,17] and confirms the ability of sites in North America to perform the initial (3-h) resuscitation bundle elements better that other regions, but also suggests that Western Europe has higher compliance with the 6-h elements.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that a critical shortage of nursing staff is one of the most important barriers to the implementation of protocol-based sepsis resuscitation in the ED [11]. The clinically beneficial effects of sepsis bundles has been confirmed in many studies performed in the ICUs of developed countries, which have relatively homogeneous conditions regarding critical care staff [5,6,[27][28][29][30]; however, to date, there have been no studies evaluating the insufficient critical care personnel to the implementation of SSC guidelines in ICUs.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have described the use of quality measures for antimicrobial sepsis treatment [20-25]. However, some indicators were not systematically developed using a Delphi method [21], and some only focused on optimal sepsis care on the ICU [20,24] or focused on the start of treatment (first 24 hours) and not on the entire clinical course [22,23,25]. …”
Section: Discussionmentioning
confidence: 99%